The Ezekiel generation : the Father's heart for Israel and the Church in the last days - Berry, Grant (Shippensburg, PA : Destiny Image Publishers, Inc., 2013)
The Father's Heart for Israel and the Church You live in one of the most critical hours in human history ... and G-d is calling you to participate! For the body of Christ to be most effective in these last days, unity is essential. We all have key roles to play in the unfolding of G-d's great agenda for history. Author Grant Berry is on a mission to help you find your place in this hour and see both Jew and Gentile unite to bring G-d's end-time purposes to fruition.
11 Lifestyle Jewish Evangelism12 Sign Here; About Grant Berry; Bonus Samples.
Description based on online resource; title from digital title page (viewed on March 16, 2018).
Master record variable field(s) change: 050, 082, 630, 650
Keywords: Bible; Bible; Messianic Judaism; Jewish Christians; RELIGION -- Biblical Studies -- Prophets; Electronic books; Textbooks